Pengenalan Ekonomi Sirkular (Circular Economy) Bagi Masyarakat Umum - Ludwina Harahap; Nurhidayati Dwiningsih (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
endangering our lives and eco-systems on this earth. They will harm and destroy human life today and the next generation. The issue of sustainability is a very interesting study to be discussed, both by activists, practitioners, relevant authorities, especially in developing countries. The concept of 3 R (Reuse, Reduce, Recycle) which has been offered as a solution to reduce industrial waste, community waste and family waste (household) continues to be developed and now we familiar with the term of circular economy concept. The concept of circular economy that is trending, must be disseminated so that every human being realizes the importance of playing a role in creating a circular economy for the survival of life in the future. This is the motive to do society empowerment activities (PKM) with the topic of Circular Economy for the societies. Even in Covid 19 pandemic era, this event (PKM) have been done physically (offline) and the targets are to make the participants understand and curious or interest about the circular economy. The result shows the understanding of circular economy from participants increased. Besides that, after following the socialization showed a change in paradigms and attitudes about the concept of circular economy and be ready to apply it in the daily life.